2022
DOI: 10.3390/su14159527
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ESG Scores on Bank Market Value? Evidence from the U.S. Banking Industry

Abstract: Although there is a large volume of literature on the relationship between Environmental, Social and Governance (ESG) and firm performance, only a limited number of studies have focused on the banking sector. In addition, most of them used linear models. Therefore, in this study, we examined the impact of ESG and ESG pillar scores (environmental, social, and governance) on the market value of U.S. commercial banks by using linear and non-linear panel regression models over the period of 2016–2020. Moreover, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…In this sense, a good ESG performance generates favorable publicity, and a company with a good ESG performance realizes higher firm value if it also enjoys favorable media coverage (Cahan et al, 2016). In conclusion, it has been found that there is a positive relationship between certain ESG factors and financial performance (Ersoy et al, 2022). Thus, our second hypothesis is as follows:…”
Section: Effect Of Environmental Social and Governance Score On Banks...mentioning
confidence: 85%
“…In this sense, a good ESG performance generates favorable publicity, and a company with a good ESG performance realizes higher firm value if it also enjoys favorable media coverage (Cahan et al, 2016). In conclusion, it has been found that there is a positive relationship between certain ESG factors and financial performance (Ersoy et al, 2022). Thus, our second hypothesis is as follows:…”
Section: Effect Of Environmental Social and Governance Score On Banks...mentioning
confidence: 85%
“…Studies in the banking sector have shown varied results. While some suggest a positive correlation between EPI and financial performance, others find no significant linear relationship (Valerio Potì, Di Martino, & Miglietta, n.d.;Ersoy et al, 2022). Moreover, theoretical frameworks and empirical evidence suggest that the relationship between EPI performance and bank value may be complex, with nonlinear associations and potential trade-offs between EPI pillars (This is supported by both theoretical frameworks and empirical evidence.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Yuen et al (2022) observed that there is a U-shaped relationship between ESG and profitability, reflecting that ESG activities improve bank performance in the long term. Ersoy et al (2022) examined 176 US commercial banks and they show an inverted U-shaped relationship between market value and ESG. Menicucci and Paolucci (2023) examine 105 Italian banks, and they show that ESG policies negatively affect ROA, ROE, stock market return and Tobin's Q, showing that Italian banks have not fully applied robust sustainability procedures.…”
Section: Profitabilitymentioning
confidence: 99%
“…(2022) observed that there is a U-shaped relationship between ESG and profitability, reflecting that ESG activities improve bank performance in the long term. Ersoy et al. (2022) examined 176 US commercial banks and they show an inverted U-shaped relationship between market value and ESG.…”
Section: Literature Background and Hypothesis Developmentmentioning
confidence: 99%